Actin Inhibition Increases Megakaryocyte Proplatelet Formation through an Apoptosis-Dependent Mechanism - Avanzi, Mauro P.; Izak, Marina; Oluwadara, Oluwasijibomi E.; Mitchell, William Beau (PloS one, 2015)
Megakaryocytes assemble and release platelets through the extension of proplatelet processes, which are cytoplasmic extensions that extrude from the megakaryocyte and form platelets at their tips. Proplatelet formation and platelet release are complex processes that require a combination of structural rearrangements. While the signals that trigger the initiation of proplatelet formation process are not completely understood, it has been shown that inhibition of cytoskeletal signaling in mature megakaryocytes induces proplatelet formation. Megakaryocyte apoptosis may also be involved in initiation of proplatelet extension, although this is controversial. This study inquires whether the proplatelet production induced by cytoskeletal signaling inhibition is dependent on activation of apoptosis. Megakaryocytes derived from human umbilical cord blood CD34+ cells were treated with the actin polymerization inhibitor latrunculin and their ploidy and proplatelet formation were quantitated. Apoptosis activation was analyzed by flow cytometry and luminescence assays. Caspase activity was inhibited by two compounds, ZVAD and QVD. Expression levels of pro-survival and pro-apoptosis genes were measured by quantitative RT-PCR. Protein levels of Bcl-XL, Bax and Bak were measured by western blot. Cell ultrastructure was analyzed by electron microscopy. Actin inhibition resulted in increased ploidy and increased proplatelet formation in cultured umbilical cord blood-derived megakaryocytes. Actin inhibition activated apoptosis in the cultured cells. The effects of actin inhibition on proplatelet formation were blocked by caspase inhibition. Increased expression of both pro-apoptotic and pro-survival genes was observed. Pro-survival protein (Bcl-xL) levels were increased compared to levels of pro-apoptotic proteins Bak and Bax. Despite apoptosis being activated, the megakaryocytes underwent minimal ultrastructural changes during actin inhibition. We report a correlation between increased proplatelet formation and activation of apoptosis, and that the increase in proplatelet formation in response to actin inhibition is caspase dependent. These findings support a role for apoptosis in proplatelet formation in this model.